Olfactory transduction pathways in the Senegalese sole Solea senegalensis - Velez, Zélia (2013)
This study tested whether differences in sensitivity between the upper and lower olfactory epithelia of Solea senegalensis are associated with different odorant receptors and transduction pathways, using the electro-olfactogram. Receptor mechanisms were assessed by cross-adaptation with amino acids (L-cysteine, L-phenylalanine and 1-methyl-L-tryptophan) and bile acids (taurocholic acid and cholic acid). This suggested that relatively specific receptors exist for 1-methyl-L-tryptophan and L-phenylalanine (food-related odorants) in the lower epithelium, and for taurocholic acid (conspecific-derived odorant) in the upper. Inhibition by U73122 [a phospholipase C (PLC) inhibitor] suggested that olfactory responses to amino acids were mediated mostly, but not entirely, by PLC-mediated transduction (IC50; 15–55 nM), whereas bile acid responses were mediated by both PLC and adenylate cyclase–cyclic adenosine monophosphate (AC–cAMP) (using SQ-22536; an AC inhibitor). Simultaneous application of both drugs rarely inhibited responses completely, suggesting possible involvement of non-PLC and non-AC mediated mechanisms. For aromatic amino acids and bile acids, there were differences in the contribution of each transduction pathway (PLC, AC and non-PLC and non-AC) between the two epithelia. These results suggest that differences in sensitivity of the two epithelia are associated with differences in odorant receptors and transduction mechanisms.